2007
DOI: 10.2113/gssgfbull.178.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Seismic noise-based methods for soft-rock landslide characterization

Abstract: Abstract. -In order to better understand the mechanics and dynamic of landslides, it is of primary interest to image correctly their internal structure and their slip surface. Several active geophysical methods are able to provide the geometry of a given landslide, but were rarely applied in 3 dimensions in the past. The main disadvantages of methods like seismic reflection and electrical tomography are that there are heavy to set up and/or to process, and they consequently are expensive and time consuming. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…The monitoring system has been complemented since 2003 by a geophysical investigation (seismic noise measurements, seismic soundings, electrical resistivity tomography; Guéguen et al, 2004;Méric et al, 2007), yielding more spatially detailed information on the geometry and depth of the slip surface and the bedrock (Tatard, 2006). These results have suggested that the slip surfaces develop first at the clay/bedrock interface where the bedrock is close to the surface and then within the clay layer.…”
Section: The Saint-guillaume Landslidementioning
confidence: 99%
See 1 more Smart Citation
“…The monitoring system has been complemented since 2003 by a geophysical investigation (seismic noise measurements, seismic soundings, electrical resistivity tomography; Guéguen et al, 2004;Méric et al, 2007), yielding more spatially detailed information on the geometry and depth of the slip surface and the bedrock (Tatard, 2006). These results have suggested that the slip surfaces develop first at the clay/bedrock interface where the bedrock is close to the surface and then within the clay layer.…”
Section: The Saint-guillaume Landslidementioning
confidence: 99%
“…The aim of this paper is to analyse quantitatively the relation between groundwater fluctuations and landslide velocity for two deep-seated landslides of the Trièves Plateau: the Monestier-du-Percy landslide (Giraud et al, 1980), and the Saint-Guillaume landslide (Azimi et al, 1994;Méric et al, 2007). First, the environmental settings of the landslides are described.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic noise correlation has been used at large scale (e.g., Shapiro et al, 2005) to infer lithospheric structures. Other methods, including the determination of spectral or horizontal-to-vertical (H/V) ratio modes, have been used at smaller scales for resonance studies of buildings, site effect estimation and engineering seismology (see e.g., Méric et al, 2007). Such analyses might be used to infer temporal variations in elastic properties of unstable rock massesas it has been already used to infer temporal variations on volcanoes (Brenguier et al, 2008) -or eventually in spectral modes, from a limited number of seismic sensors.…”
Section: Introductionmentioning
confidence: 99%
“…More recent applications of noise based techniques are microzonation studies based on seismic site response (Parolai et al, 2004), in the study of dynamical behaviour of buildings (Gallipoli et al, 2010;Nakata et al, 2013), crustal tomography through noise correlation techniques (Curtis et al, 2006), shallow crustal velocity profiling (Panzera & Lombardo 2013), monitoring of earth dams and levees by noise interferometry (Planès et al, 2015(Planès et al, , 2017, underground mining (Olivier et al, 2015 ) as well as active volcanoes (Ballmer et al, 2013;Cannata et al, 2017). Noise data can also potentially provide high resolution spatio-temporal information about the landscape dynamics and evolution (Méric et al, 2007). The sources of noise are usually dynamic in nature because of this dynamism the levels of noise in a region are not constant over time.…”
Section: Introductionmentioning
confidence: 99%